Comparative evaluation of table egg quality of local and pure breed laying hens in response to storage period length - Metin PETEK; Tuğba KAHRAMAN (Kafkas Universitesi Veteriner Fakültesi Dergisi)
This study was made to investigate the fresh and stored egg quality characteristics of local and pure-breed layer chickens. The eggs were randomly collected from a commercial farm that raised different free-range layer flocks such as local Atak-S, commercial Nick Brown, pure-breed Sussex laying hen, and a local cross-breed hen, all of 50 weeks of age. In total, 240 eggs, 60 eggs from each genotype, were further divided into three groups as: fresh eggs, 15 and 28-day storage period, and were stored at 14-16°C and 45- 50% humidity conditions. The eggs were analyzed on the basis of internal and external quality, such as egg length, egg width, color characteristics, yolk height, albumin height, yolk color, and Haugh unit. Genotype had a significant effect on shell weight (P<0.001), shell thickness (P<0.001), albumen index (P<0.001), yolk index (P<0.001), and HU value (P<0.003). The effects of the storage period on albumen index, yolk index, and HU value were found to be significant, respectively (P<0.001, P<0.001, P<0.001). Significant differences existed for the shape index, L*, a*, b*, E, and C* values among the genotype groups (P<0.001). In conclusion, eggs of the local, pure-breed, and cross-breed layer chickens showed differences from the eggs of commercial hybrid hens both for external and internal quality. Eggs of commercial Nick Brown and Sussex breed seems slightly better in longer storage conditions.